Bioactivatable reactive oxygen species-sensitive nanoparticulate system for chemo-photodynamic therapy. (May 2020) - Kim, Yugyeong; Uthaman, Saji; Pillarisetti, Shameer; Noh, Kangmin; Huh, Kang Moo; Park, In-Kyu
Abstract: Bioactivatable polymer nanoparticles (NPs) have attracted considerable attention as a prospective cancer therapy. Herein, we describe bioactivatable reactive oxygen species (ROS)-sensitive prodrug NPs designed to elicit spatiotemporally controlled, phototriggered chemo-photodynamic therapy. First, an effective anticancer agent, doxorubicin (DOX), was conjugated to poly(ethylene glycol) (PEG) via an ROS-responsive degradable thioketal (TK) linker. The resulting amphiphilic PEG-DOX conjugate (PEG-TK-DOX) self-assembled into a bioactivatable ROS-responsive NP system could efficiently encapsulate a hydrophobic photodynamic therapy (PDT) agent, pheophorbide A (PhA), with good colloidal stability and unimodal size distribution. Second, after the selective retention of NPs in the tumor, the site-specific release of DOX and PhA was spatiotemporally controlled, initially by endogenous ROS and subsequently by exogenous ROS produced during PDT. The locoregional treatment not only photoactivates PhA molecules to generate cytotoxic ROS but also triggers an ROS cascade, which accelerates the release of DOX and PhA via the ROS-mediated structural destruction of NPs, resulting in an enhanced anticancer therapeutic effect. This prodrug-NP system may function as an effective nanomedicine platform, working synergistically to maximize the efficacy of the combination of chemotherapy and photodynamic therapy with a remote-controlled release mechanism. Statement of significance: Photodynamic therapy (PDT) is a noninvasive therapy involving local ROS generation through the activation of photosensitizer (PS) molecules induced via external irradiation with near-infrared (NIR) light. Combinational therapies with PDT could synergistically enhance the therapeutic efficacy and overcome the limitations of monotherapy. In this study, we describe bioactivatable reactive oxygen species (ROS)-sensitive prodrug nanoparticles designed to elicit spatiotemporally controlled, photo triggered chemo-photodynamic therapy. Upon accumulation in tumor by enhanced permeation and retention (EPR) effect, the nanoparticles exhibited target-specific release of chemo-drug and photosensitizer in a spatiotemporally controlled cascade manner by endogenous ROS in the initial stage and the excessive production of exogenous ROS during PDT, leading to a further ROS cascade that accelerates the release of therapeutic cargo. Graphical abstract: Image, graphical abstract